Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Certainly! Let's explore this step by step.
Given:
- \( A \) is a square matrix such that \( A^2 = A \).
- We need to find the expression for \( (1 + A)^3 - 7A \).
First, let's understand the property of \( A \):
- Since \( A^2 = A \), \( A \) is known as an idempotent matrix.
Now, let's simplify the expression \( (1 + A)^3 - 7A \) step by step.
1. We will use the binomial expansion to expand \( (1 + A)^3 \).
[tex]\[ (1 + A)^3 = 1 + 3A + 3A^2 + A^3 \][/tex]
2. We know from the given property of the matrix \( A \) that \( A^2 = A \). Therefore:
[tex]\[ A^2 = A \quad \text{and} \quad A^3 = A^2 \cdot A = A \cdot A = A \][/tex]
3. Substituting these results back into the binomial expansion:
[tex]\[ (1 + A)^3 = 1 + 3A + 3A + A = 1 + 3A + 3A + A \][/tex]
4. Combine like terms:
[tex]\[ (1 + A)^3 = 1 + 7A \][/tex]
Now, we need to find \( (1 + A)^3 - 7A \):
[tex]\[ (1 + A)^3 - 7A = (1 + 7A) - 7A \][/tex]
5. Simplify by subtracting \( 7A \):
[tex]\[ (1 + 7A) - 7A = 1 + 7A - 7A = 1 \][/tex]
Therefore, the expression \( (1 + A)^3 - 7A \) simplifies to:
[tex]\[ \boxed{1} \][/tex]
Given:
- \( A \) is a square matrix such that \( A^2 = A \).
- We need to find the expression for \( (1 + A)^3 - 7A \).
First, let's understand the property of \( A \):
- Since \( A^2 = A \), \( A \) is known as an idempotent matrix.
Now, let's simplify the expression \( (1 + A)^3 - 7A \) step by step.
1. We will use the binomial expansion to expand \( (1 + A)^3 \).
[tex]\[ (1 + A)^3 = 1 + 3A + 3A^2 + A^3 \][/tex]
2. We know from the given property of the matrix \( A \) that \( A^2 = A \). Therefore:
[tex]\[ A^2 = A \quad \text{and} \quad A^3 = A^2 \cdot A = A \cdot A = A \][/tex]
3. Substituting these results back into the binomial expansion:
[tex]\[ (1 + A)^3 = 1 + 3A + 3A + A = 1 + 3A + 3A + A \][/tex]
4. Combine like terms:
[tex]\[ (1 + A)^3 = 1 + 7A \][/tex]
Now, we need to find \( (1 + A)^3 - 7A \):
[tex]\[ (1 + A)^3 - 7A = (1 + 7A) - 7A \][/tex]
5. Simplify by subtracting \( 7A \):
[tex]\[ (1 + 7A) - 7A = 1 + 7A - 7A = 1 \][/tex]
Therefore, the expression \( (1 + A)^3 - 7A \) simplifies to:
[tex]\[ \boxed{1} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.